2017
DOI: 10.1007/s11356-017-9394-6
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and human health risk assessment of PAHs in four fish species from a SW Atlantic estuary

Abstract: The aim of this study is to assess-for the first time-the concentration of the 16 polycyclic aromatic hydrocarbons (PAHs) in the muscle tissues of four fish species (Micropogonias furnieri, Cynoscion guatucupa, Ramnogaster arcuata, and Mustelus schmitti) from Bahía Blanca estuary, Argentina and to evaluate their sources, distribution, and the human health risks implicated. Considering the four species under study, mean total PAH concentrations showed the following decreasing accumulation trend: M. schmitti, R.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 51 publications
1
16
1
Order By: Relevance
“…Higher concentrations of ∑cPAHs were found in fish at high trophic levels, such as snakeheads and sturgeons, wileyonlinelibrary.com/ETC © 2019 SETAC Contribution of PAHs via aquaculture product consumption-Environmental Toxicology and Chemistry, 2019;38:1084-1092 indicating different dietary compositions compared with crab, prawn, and shellfish. The ∑cPAH concentrations in the present study were higher than those in fish from an Atlantic estuary (0.90-84 ng/g dry wt) investigated by Oliva et al (2017) and from the remote upstream area of the Yangtze River (1.2-2.4 ng/g dry wt) measured by Wang et al (2016).…”
Section: Concentrations Of Pahs In Freshwater Aquaculture Products Frcontrasting
confidence: 76%
“…Higher concentrations of ∑cPAHs were found in fish at high trophic levels, such as snakeheads and sturgeons, wileyonlinelibrary.com/ETC © 2019 SETAC Contribution of PAHs via aquaculture product consumption-Environmental Toxicology and Chemistry, 2019;38:1084-1092 indicating different dietary compositions compared with crab, prawn, and shellfish. The ∑cPAH concentrations in the present study were higher than those in fish from an Atlantic estuary (0.90-84 ng/g dry wt) investigated by Oliva et al (2017) and from the remote upstream area of the Yangtze River (1.2-2.4 ng/g dry wt) measured by Wang et al (2016).…”
Section: Concentrations Of Pahs In Freshwater Aquaculture Products Frcontrasting
confidence: 76%
“…For example, fish are considered to have a higher metabolism capacity and can metabolize/depure PAHs quickly; therefore, a generally positive correlation between the concentration of PAHs in the body and the K ow value is not observed in higher trophic-level fish [134]. Additionally, several previous studies suggested that species differences in the metabolism capacity of PAHs are strongly suggested for fish and invertebrates [138][139][140]. These differences may be caused by species differences in intake pathway and efficiency, capacity of xebiotics to metabolize, and ability of depuration/excretion.…”
Section: General Trend Of the Bioaccumulation Of Pahs In Aquatic Orgamentioning
confidence: 99%
“…For example, Cheung et al [146] detected higher concentrations of PAHs in the carnivorous fish golden threadfin bream Nemipterus virgatus and catfish Clarias fuscus compared with herbivorous/omnivorous fish. It is difficult to obtain a consensus on the PAH-accumulation trend in fish among trophic levels due to their huge differences in PAH bioavailability and habitat between species [140,150,159,160]. Oligochaete worms Lake Erie 8 300-400 (range) Eadie et al [154] Chironomid midges Lake Erie 8 400-800 (range) Eadie et al [154] Bivalves: Zebra mussel Detroit River and western Lake Erie 16 USEPA priority 12.6-8.7 (range) Metcralfe et al [156] Note.…”
Section: Bioaccumulation Of Pahs In Fishmentioning
confidence: 99%
See 1 more Smart Citation
“…where C i is the concentration of the individual PAH in fish muscle (ng/g ww), and TEFi is the corresponding toxic equivalency factor related to BaP (Nisbet and LaGoy 1992).…”
Section: Human Health Risk Assessmentmentioning
confidence: 99%